Fronts de terres, géographie des relations urbaines et rurales par le biais des terres excavées en Île-de-France - Marie-Laure Garnier; Patrick Moquay (Projets de Paysage)
The way we build cities generates considerable volumes of excavated soil. This transfer of soil from the city to the outlying rural areas causes tensions. The financial windfall from the removal and storage of these soils is countered by problems of social and environmental acceptance in the receiving areas. We analyse the mechanisms at work in the production of excavated soils before looking at the counterpart of this economy in rural areas while seeking to understand the logic behind the selection of areas as outlets for excavated soils and inert materials. Awareness of this geography involving a profound physical modification of the landscapes concerned encourages us to look for new ways of relating to urban soils and their use in landscape projects. This raises the question of how landscape architects may support this transformation in the management of urban soils, from the production to the reception of excavated soils.